C ; Theoretical frameworks for a productivity and efficiency analysis of agricultural enterprises - Aleksej Lissitsa; Tamara Babiéceva (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2003)
" " . , , , . . , a , a . " ", , , . – – The main aim of this Discussion Paper is to acquaint the Russian-speaking reader with theoretical issues of the efficiency and productivity analysis of the agricultural enterprises. In the Russian-speaking literature at the analysis of efficiency of the enterprises, as a rule, were used and are used up to today's time parameters of profitability, which value are compared on the separate enterprises or their groups. In this study the most widespread methods of productivity and efficiency analysis are presented. The analysis is structured in the following way: a overview of the most theoretical points about differences between efficiency and productivity is followed by an explanation of the methodological foundation of productivity and efficiency measurement techniques. Malmquist, Törnkvist and Fisher Indexes are presented more detailed.
urn:nbn:de:gbv:3:2-23259
Keywords: B4; C6; D2; O3; O4; 330; Productivity; Efficiency; Index Number Theory; Malmquist; Törnkvist; Fisher Index